E-cigarette knowledge and use among undergraduate students in Oman: a cross-sectional study - Wafa Al Jabri; Ali Bani Oraba; Sultan Bani Oraba; Lui Al Nadhiri; Osama Al Jamoudi (International Journal of Public Health Science (IJPHS), 2026)
The increasing prevalence of electronic cigarette (e-cigarette) uses among youth globally, including in Oman, raises significant public health concerns. Despite a ban on the sale and marketing of e-cigarettes in Oman since 2015, their use remains legal and has increased among university students. This study aims to assess e-cigarette knowledge among students at Sultan Qaboos University (SQU) and examine its association with e-cigarette use. It addresses a gap in the Omani literature, where evidence on e-cigarette knowledge and use among university students remains limited despite existing regulatory restrictions. A cross-sectional survey was conducted to gather data on students' knowledge, and use of e-cigarettes. Among 449 university students, overall knowledge of e-cigarettes was relatively high, with most participants acknowledging their potential health risks and supporting regulatory measures; however, some misconceptions still remained. Students from scientific colleges showed significantly higher knowledge levels than those from humanities colleges (p < 0.05). Although only 12.7% reported ever using e-cigarettes, there was a significant negative correlation between knowledge and use (r = -0.245, p < 0.001), indicating that higher knowledge was associated with lower likelihood of e-cigarette use. The findings suggest the importance of strengthening health education and regulatory efforts to improve e-cigarette awareness and reduce use among university students in Oman.